Acute Kidney Injury and Renal Replacement Therapy in Burns - Burak Canver (Galenos Yayinevi, 2011)
Acute kidney injury (AKI) is a common complication in patients with severe burn injury and one of the major causes of death. It has a negative prognostic value and almost always develops in the context of multiple organ dysfunction syndrome (MODS) induced by sepsis. Over the last 20 years, according to data avaliable, the mortality rate has been reported to reach about 75%. Several definitions of AKI have been used , but nowadays the RIFLE classification is considered the gold standard, enabling a more objective comparison of populations. There are several ways to treat AKI in burn patients, including peritoneal dialysis (PD), intermittent hemodialysis, and continuous renal replacement therapy (CRRT). CRRT is generally used in patients in whom intermittent hemodialysis has failed to control hypovolemia, as well as in patients who cannot tolerate intermittent hemodialysis. Additionally, PD is not suitable for patients with burns within the abdominal area. For these reasons, most patients with unstable hemodynamic conditions receive CRRT. In burn patients with acute renal failure the dialytic treatment with continuous renal replacement therapies permitted us to achieve a survival and dialytic adequacy; however, mortality rate is high and related to septic shock and MODS. Despite the wide variation of the analysed burn populations and definitions of AKI, this review clearly showed that AKI remains prevalent and is associated with increased mortality in patients with severe burn injury. (Journal of the Turkish Society Intensive Care 2011; 9 Suppl: 46-50)